1986
DOI: 10.1038/bjc.1986.111
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and lung cancer with special regard to type of smoking and type of cancer. A case-control study in north Sweden

Abstract: Summary The aetiologic role of tobacco smoking was elucidated in a case-control study comprising 579 cases of male lung cancer registered during [1972][1973][1974][1975][1976][1977]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…5,34 -36,38,43,45,48 -50,53,54 Eleven studies 31-33,37,39 -42,46,51,55 used hospital-based control subjects, and only 2 studies 6,44 were autopsybased. The study of Damber and Larsson 47 used both population-based and autopsy-based control subjects, and data pertaining to population-based control subjects were used in the meta-analysis. The study of Ger et al 52 used both hospital-based and population-based control subjects and was considered as a population-based study in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,34 -36,38,43,45,48 -50,53,54 Eleven studies 31-33,37,39 -42,46,51,55 used hospital-based control subjects, and only 2 studies 6,44 were autopsybased. The study of Damber and Larsson 47 used both population-based and autopsy-based control subjects, and data pertaining to population-based control subjects were used in the meta-analysis. The study of Ger et al 52 used both hospital-based and population-based control subjects and was considered as a population-based study in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The study of Ger et al 52 used both hospital-based and population-based control subjects and was considered as a population-based study in the analysis. Nine studies 5,6,33,44,45,47,51,53,54 were restricted to men, and four studies 35,43,49,50 were restricted to women. Twelve studies 32,34,36 -42,46,48,55 reported data separately for both men and women.…”
Section: Resultsmentioning
confidence: 99%
“…A connection between tobacco smoking and lung cancer was found early in Norwegian studies (17), and was later well established (18). A dose-response relation between tobacco consumption and lung cancer is found in most studies (4,19,20). In Northern Sweden, an increase in the smoking prevalence was followed by an increase in lung cancer mortality (21).…”
Section: Figure 3 Incidence Of Lung Cancer In Norwegian Counties 1990mentioning
confidence: 97%
“…The major risk factor for the development of lung cancer has been clearly established. An increased number of cigarettes smoked and duration of smoking lead to higher risks of developing lung cancer [2]. The sooner one is able to quit smoking, the lower their likelihood of developing lung cancer will be, though this risk never quite approaches that of a never smoker [3].…”
Section: The Problemmentioning
confidence: 99%